Application of Lane’s cut-off grade model to a gold open pit mining project - Lino Arias (Instituto de Ingenieros de Minas del Peru, 2017)
The main objective of this project is to review and develop a comprehensive application of Lane’s cut-off grade model to a case study, as well as to compare its principles and results compared to break-even cut-off grade model utilisation under the same conditions. The case study sets the context of the application: A conceptual study of a gold open pit mining project requires a cut-off grade analysis, which consists in develop a cut-off grade policy that maximises the net present value (NPV) using Lane’s and break-even model.